Estudos bio-ecologicos de Bracon vulgaris ashmead (Hymenoptera: braconidae), ectoparasito de anthonomus grandis Boheman, 1843 (Coleoptera: curculionidae) - Carvalho, Sergio Luis de (1994)
Orientador: Mohamed E. M. Habib